Pengaruh Karateristik Petani pada Produktivitas Usahatani Jagung Manis di Kecamatan Rasau Jaya Kabupaten Kubu Raya - Fatricia, Angelina; Yurisinthae, Erlinda; Dolorosa, Eva (Universitas Galuh, 2025)
The productivity of sweet corn in Kubu Raya Regency is still low even though sweet corn is one of the most profitable cultivation groups. This research aims to analyze the influence of age, education, experience and family support on swet corn productivity. This research was conducted from February to June 2024. This type of research is descriptive research with a quantitative approach. The sample in this study was 100 sweet corn farmers in Rasau Jaya Satu Village and Rasau Jaya Dua Village, Rasau Jaya District, Kubu Raya Regency, West Kalimantan Province. Data collection techniques were carried out by interviews and filling out questionnaires directly. Testing research instruments uses validity and reliability tests. The data analysis technique uses multiple linear regression analysis by testing classical assumptions first with SPSS version 23 software. The results of the research show that the four variables, namely age, education, experience and family dependents, have an effect on sweet corn productivity. Experience in farming sweet corn has a positive effect because experience will make farmers understand the environmental conditions where they are farming and know the problems and be able to find solutions when carrying out farming activities. The longer someone does their job, the more skilled, diligent, painstaking and qualified they will be. There is a need to improve skills and strategies for allocating time working outside the agricultural sector and continuing to work side jobs in the agricultural sector so that productivity can increase with more efficient time.